Analysis of prognostic factors affecting immune checkpoint inhibitor therapy in tumor patients exposed to antibiotics - Qian Chen; Zhen Zhang; Xiaoli Li; Shaomei Feng; Shui Liu (Frontiers in Oncology, 2023)
ObjectiveMeta-analysis was performed to evaluate the prognostic factors in tumor patients treated with immune checkpoint inhibitors (ICIs) under antibiotic exposure.MethodLiterature on the effect of antibiotics on the prognosis of tumor patients receiving ICIs was retrieved from Pubmed, Cochrane Library, EMbase, EBSCO Evidence-Based Medicine Database, China Biomedical Literature Database (CBM), and China National Knowledge Network (CNKI), and relevant influencing factors were extracted. Meta-analysis of efficacy was performed using RevMan 5.4 software.ResultsA total of nine studies for 1,677 patients were included. The meta-analysis results showed that, in terms of progression-free survival, gender (male vs. female), Eastern Cooperative Oncology Group performance status (ECOG PS) (1–2 vs. 0), history of another cancer (yes vs. no), liver metastasis (yes vs. no), antibiotics (within the previous 2 months), PD-L1 (1%–49%), and PD-L1 (≥50%) factors are associated with progression-free survival in patients treated with ICIs under antibiotic exposure. In terms of overall survival, gender (male vs. female), ECOG score (1–2 vs. 0), history of another cancer (yes vs. no), brain metastasis (yes vs. no), liver metastasis (yes vs. no), radiation (within the previous 3 months), antibiotics (within the previous 2 months), PD-L1 (1%–49%), and PD-L1 (≥50%) factors are associated with overall survival in patients with antibiotic exposure receiving ICIs for tumor treatment.ConclusionGender, ECOG score, history of another cancer, brain metastasis, liver metastasis, radiation (within the previous 3 months), antibiotics (within the previous 2 months), PD-L1 (1%–49%), and PD-L1 (≥50%) were associated with clinical benefit in patients with antibiotic exposure receiving ICIs for tumor treatment. Based on the above-mentioned factors, clinicians can screen cancer patients who receive ICIs under antibiotic exposure and rationally use antibiotics and ICIs in combination.